Prefrontal photobiomodulation produces beneficial mitochondrial and oxygenation effects in older adults with bipolar disorder - O’Donnell, Courtney M.; Barrett, Douglas W.; O’Connor, Patrick; Gonzalez-Lima, F. (Frontiers in Neuroscience, 2023)
There is growing evidence of mitochondrial dysfunction and prefrontal cortex (PFC) hypometabolism in bipolar disorder (BD). Older adults with BD exhibit greater decline in PFCrelated neurocognitive functions than is expected for age-matched controls, and clinical interventions intended for mood stabilization are not targeted to prevent or ameliorate mitochondrial deficits and neurocognitive decline in this population. Transcranial infrared laser stimulation (TILS) is a non-invasive form of photobiomodulation, in which photons delivered to the PFC photo-oxidize the mitochondrial respiratory enzyme, cytochrome-c-oxidase (CCO), a major intracellular photon acceptor in photobiomodulation. TILS at 1064-nm can significantly upregulate oxidized CCO concentrations to promote differential levels of oxygenated vs. deoxygenated hemoglobin (HbD), an index of cerebral oxygenation. The objective of this controlled study was to use non-invasive broadband near-infrared spectroscopy to assess if TILS to bilateral PFC (Brodmann area 10) produces beneficial effects on mitochondrial oxidative energy metabolism (oxidized CCO) and cerebral oxygenation (HbD) in older (>50 years old) euthymic adults with BD (N=15). As compared to sham, TILS to the PFC in adults with BD increased oxidized CCO both during and after TILS, and increased HbD concentrations after TILS. By significantly increasing oxidized CCO and HbD concentrations above sham levels, TILS has the potential ability to stabilize mitochondrial oxidative energy production and prevent oxidative damage in the PFC of adults with BD. In conclusion, TILS was both safe and effective in enhancing metabolic function and subsequent hemodynamic responses in the PFC, which might help alleviate the accelerated neurocognitive decline and dysfunctional mitochondria present in BD.